Aminoguanidine Protects Boar Spermatozoa against the Deleterious Effects of Oxidative Stress - Pintus, Eliana; Kadlec, Martin; Jovičić, Marija; Sedmíková, Markéta; Ros-Santaella, José Luis (Pharmaceutics, 2018)
Aminoguanidine is a selective inhibitor of the inducible nitric oxide synthase (iNOS) and a scavenger of reactive oxygen species (ROS). Numerous studies have shown the antioxidant properties of aminoguanidine in several cell lines, but the in vitro effects of this compound on spermatozoa under oxidative stress are unknown. In this study, we tested the hypothesis that aminoguanidine may protect against the detrimental effects of oxidative stress in boar spermatozoa. For this purpose, sperm samples were incubated with a ROS generating system (Fe2+/ascorbate) with or without aminoguanidine supplementation (10, 1, and 0.1 mM). Our results show that aminoguanidine has powerful antioxidant capacity and protects boar spermatozoa against the deleterious effects of oxidative stress. After 2 h and 3.5 h of sperm incubation, the samples treated with aminoguanidine showed a significant increase in sperm velocity, plasma membrane and acrosome integrity together with a reduced lipid peroxidation in comparison with control samples (p < 0.001). Interestingly, except for the levels of malondialdehyde, the samples treated with 1 mM aminoguanidine did not differ or showed better performance than control samples without Fe2+/ascorbate. The results from this study provide new insights into the application of aminoguanidine as an in vitro therapeutic agent against the detrimental effects of oxidative stress in semen samples.
Keywords: lipid peroxidation; sperm velocity; oxidative stress; nitric oxide; antioxidant capacity